A potencialização da resiliência organizacional e da competitividade de empresas do segmento de estética e beleza no contexto da pandemia pelo COVID-19 - Altmann, Marselha Vianna (Universidade do Vale do Rio dos Sinos, 2022)
Organizational resilience can also be associated with a kind of reengineering aimed at innovation with technological and organizational disruptions and even the redesign of social roles in order to break with previous models and innovate completely. It should be noted that, in this context, continuous improvements imply the incremental and progressive improvement of the organization’s existing processes, products and/or services. Thus, the main objective of the research is to propose directions to enhance the organizational resilience and competitiveness of companies in the context under study (micro and small companies in the aesthetic and beauty segment, more specifically hairdressers, manicurist and pedicurist located in the cities of Porto Alegre and Canoas, located in metropolitan region of the State of RS). Therefore, a qualitative exploratory research was carried out. Data were collected by means ten individual in-depth interviews, with a semi-structured approach; while its data analysis was implemented from content analysis. This research contributes to verify the adequate allocation of available resources and capabilities to enhance the resilience and competitiveness of organizations in the aesthetics and beauty segment. As a result, two types of entrepreneur profiles were identified, conservative and aggressive, which differently articulated the available resources, evidencing that organizational capabilities fostered differentials to survive and stand out during the pandemic (Covid-19).
Keywords: Resiliência organizacional; Estratégia; Recursos; Capacidades; Gestão de operações; Competitividade; Organizational resilience; Strategy; Resources; Capabilities; Operations management; Competitiveness; ACCNPQ::Ciências Sociais Aplicadas::Administração